A CHURCH DIVIDED: ROMAN CATHOLICISM, AMERICANIZATION, AND THE SPANISH-AMERICAN WAR1. (22nd July 2015) - Wetzel, Benjamin
Abstract: Standard accounts of American Catholic history generally note in passing that American Catholics supported the Spanish-American War but do not examine what reasons provoked them to do so. At the same time, recent literature on the war itself has described various factors that motivated American support, but few of these studies have noted the central role that religion played in Americans' interpretations of the conflict. This article brings these two historiographies together by showing the importance of the war for the Catholic Church in America as well as the significance of religious belief for how many Americans understood the conflict. In particular, providentialist interpretations of the war held by a large number of Catholics reveal a crucial moment in the church's process of Americanization. Yet more importantly, this article focuses on the significant number of Catholics who steadfastly opposed the war, demonstrating the contested nature of the Americanization process. Ultimately, this article maintains that skepticism concerning the righteousness of the American nation motivated antiwar Catholics' resistance to prevalent American attitudes. By integrating American Catholics into our understanding of the Spanish-American War, this article sheds new light on the development of fin de siècle American Catholicism and on the war itself.